Pengaruh Keputusan Investasi, Keputusan Pendanaan, Kebijakan Dividen Dan Kinerja Keuangan Terhadap Nilai Perusahaan (Study Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2014) - Rudiyanto, Rudiyanto, Dr. Erma Setiawati, Ak, MM (2016)
The purpose of this study aims to determine the effect of investment decisions (PER), Funding Decisions (DER), Dividend Policy (DPR), and Financial Performance (ROA) partially and simultaneously to Company Value in Manufacturing Company in Indonesia Stock Exchange Period 2011-2014. The period used in this study is 4 years starting in 2011-2014. The population used in this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2011-2014. This study using purposive sampling method for sampling. Based on predetermined criteria, the number of samples collected as many as 18 companies. Statistical analysis in this study using multiple linear regression analysis. The results of this study indicate that the investment decision (PER) significantly affects the value of the company, the funding decision (DER) no significant effect on the value of the company, dividend policy (DPR) had no significant effect on corporate value and financial performance (ROA) has no significant effect on the value company Keywords : investment decision, financing decision, dividend policy, financial performance, the company's value